Improvement of Bentonite Soil Strength Using Glass Powder - Ismael, Manal Maher; Barwari, Mateen Ibrahim Ahmed; Ahmed, Ahmed Mohammed; Aksoy, H. Suha (Dr D. Pylarinos, 2025)
This study examines how adding powdered glass at 10%, 20%, and 25% improves the strength properties of bentonite soil. Laboratory tests, including Atterberg limits, compaction, California Bearing Ratio (CBR), and Unconfined Compressive Strength (UCS), were conducted to evaluate the effects of glass powder. The results indicate that increasing the glass powder decreases soil plasticity, with reductions in Liquid Limit (LL) and Plasticity Index (PI), while the Maximum Dry Density (MDD) increased from 16.5 g/cm3 to 17.1 g/cm3 and the Optimum Moisture Content (OMC) decreased from 16% to 14%. The CBR values improved notably, rising from 18.8% to 48.2% at 0 days, and reaching 179.9% in 28 days with 10% glass powder, although higher percentages showed variable long-term results. UCS also increased from 33.3 kg/cm2 to 56.5 kg/cm2 at 0 days and from 156.2 kg/cm2 to 211.6 kg/cm2 at 28 days, as the glass content increased. These improvements are due to the pozzolanic reactions between the glass powder and soil minerals, which enhance the particle bonding and soil strength. The study concludes that adding glass powder effectively strengthens bentonite soil, with 10% identified as the optimal amount for strength enhancement and material efficiency. © (c) by the authors
Keywords: California Bearing Ratio; glass powder; soil stabilization; unconfined compressive strength